Characteristics of Modes in Photonic Crystal Fibers - Altfat Radi Jlod (Journal of Global Pharma Technology, 2019)
In this article, both the vector effect index method (VEIM) and finite element method (FEM) are exploited to calculate the effective index of FSM for the solid-and porous core PCF. For the solid-core, the EIM applies one time to estimate the equivalent cladding index. Then, the conventional characteristics’ equation will apply to construct the 14neff"> . For porous-core PCF, the EIM applies two times one for the core and other for cladding. Next, also the conventional characteristic equation will apply to explain the 14neff">  at the porous-core PCF.Keywords: Finite element method, Porous core PCF, Vector effect method.